2013
DOI: 10.1016/j.toxicon.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of proteases in the injected and dissected venom of cone snail species

Abstract: The venom of cone snails has been the subject of intense studies because it contains small neuroactive peptides of therapeutic value. However, much less is known about their larger proteins counterparts and their role in prey envenomation. Here, we analyzed the proteolytic enzymes in the injected venom of Conus purpurascens and Conus ermineus (piscivorous), and the dissected venom of Conus purpurascens, Conus marmoreus (molluscivorous) and Conus virgo (vermivorous). Zymograms show that all venom samples displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…This mass range of peptides is not unique to ant venoms, as cone snail venom contains mostly low molecular weight peptides in their venoms 55 . Nevertheless, other venomous organisms such as spiders 13 and scorpions have peptides in the higher molecular weight range of approximately 3-10 kDa 9,56 . However, comparison of individual masses within ant venom LC fractions found that each collection method resulted in venoms with unique peptide masses.…”
Section: Variations In Peptidomementioning
confidence: 99%
See 3 more Smart Citations
“…This mass range of peptides is not unique to ant venoms, as cone snail venom contains mostly low molecular weight peptides in their venoms 55 . Nevertheless, other venomous organisms such as spiders 13 and scorpions have peptides in the higher molecular weight range of approximately 3-10 kDa 9,56 . However, comparison of individual masses within ant venom LC fractions found that each collection method resulted in venoms with unique peptide masses.…”
Section: Variations In Peptidomementioning
confidence: 99%
“…For example, 12% of the dry weight of bumblebee venom are PLA2s 75 . The lipase property of phospholipases may also facilitate further spreading of venom through the host tissue 13 .…”
Section: Variations In Proteomementioning
confidence: 99%
See 2 more Smart Citations
“…Since both forms of the venom reside in the venom duct, the dissected venom is a mix of predatory venom vs. defensive venom [17] and thus more complex for this reason alone. We have previously shown that conoproteins are important components in the injected venom of C. purpurascens and C. ermineus [49], but evaluating the differential expression of proteins in the venom requires more elaborated approaches.…”
Section: Comparison Of the Injected Venom And The Dissected Venom By mentioning
confidence: 99%